Open-Access Geographic Sources And Data For The Study And Management Of Natural Resources - TUESTA, RONALD PUERTA; ESENARRO, DORIS; MINGA, CESAR; RODRIGUEZ, CIRO; AYLAS, CARMEN (The journal of contemporary issues in business and government, 2021)
The objective of this systematic review is to describe and analyze open geographic data provided by governmental sources in order to provide an overview of open geographic sources and data for the study and management of natural resources in Peru. For this purpose, the web was explored and scientific articles were reviewed, finding a huge cartographic archive offered by the Peruvian State. On the one hand, public institutions put their respective geoportals into operation, and on the other hand, the launching into space of the PeruSAT-1 satellite. This increased the supply of official geospatial information in the last five years. In addition, geotechnical data was found in raw and processed form from global initiatives. All of this documentary collection is available to the public in an open, free and free form in cyberspace, which can be used in the study of the use, restoration, conservation and valuation of ecosystems and other elements of the environment.